Adsorptive removal of trinitrophenol using nano α-Fe2O3/reduced graphene oxide. Issue 7 (2nd July 2020) - Khurana, Ishani; Shaw, Ajay Kumar; Bharti,; Khurana, Jitender M.; Rai, Pramod Kumar
Abstract: 2, 4, 6-Trinitrophenol (TNP), an explosive utilized for artillery munitions, ends up polluting water and soil. This study targets the treatment of TNP contaminated water via adsorption technique. A comparative adsorption study using pristine rGO (reduced graphene oxide), α-Fe2 O3 /rGO, bare α-Fe2 O3 and physical mixture of α-Fe2 O3 & rGO has been carried to select the most suitable adsorbent. To understand the mechanism of adsorption of TNP on α-Fe2 O3 /rGO adsorption isotherms were applied on adsorption data. The adsorption kinetics followed pseudo second order kinetic model. The mechanism of adsorption changed significantly with change in pH. The maximum adsorption capacity was found to be 769.23 mg · g −1 . Regeneration studies indicated that the adsorbent can be used up to 3 times without significant decrease in adsorption efficiency. Magnetic nature of adsorbent allowed its easy segregation from the contaminant solution upon application of external magnetic field. To assess the adsorption efficacy of α-Fe2 O3 /rGO in real water under ambient condition, TNP was spiked in ground water samples collected from adjoining district that had high TDS (Total dissolved solids). The Langmuir adsorption capacity of 164.24 mg · g −1 was attained with substantial decrease in TDS. Thus α-Fe2 O3 /rGO proves to be an efficient adsorbent for nitrophenols and can be used commercially for waste water treatment.